Physical Function Does Not Predict Care Assessment Need Score in Older Veterans. (March 2019) - Serra, Monica C.; Addison, Odessa; Giffuni, Jamie; Paden, Lydia; Morey, Miriam C.; Katzel, Leslie
Objective: The Veterans Health Administration's Care Assessment Need (CAN) score is a statistical model, aimed to predict high-risk patients. We were interested in determining if a relationship existed between physical function and CAN scores.Method: Seventy-four older (71 ± 1 years) male Veterans underwent assessment of CAN score and subjective (Short Form–36 [SF-36]) and objective (self-selected walking speed, four square step test, short physical performance battery) assessment of physical function.Results: Approximately 25% of participants self-reported limitations performing lower intensity activities, while 70% to 90% reported limitations with more strenuous activities. When compared with cut points indicative of functional limitations, 35% to 65% of participants had limitations for each of the objective measures. Any measure of subjective or objective physical function did not predict CAN score.Conclusion: These data indicate that the addition of a physical function assessment may complement the CAN score in the identification of high-risk patients.